2015
DOI: 10.1111/jam.12907
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of type 41 and high sequence diversity of partial hexon gene of human adenoviruses in municipal raw sewage and activated sludge

Abstract: High-throughput-sequencing results provided better insights of HAdV distribution and genetic diversity for raw sewage and AS samples allowing some probable biases for cloning-sequencing approach to be defeated and further providing public health awareness regarding viral-contaminated sewages or sludges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The increase in the prevalence of HAdV may be associated with antigenic drift [52][53][54]. In water matrices, the genotype 41 is also the most prevalent genotype in several regions worldwide such as Michigan, Poland, Norway, South Africa, Tunisia, Taiwan, Singapore, Germany, Italy [10,29,31,32,[55][56][57][58]. These data strengthen the results obtained in this study that also point the genotype 41 as the most prevalent in the capital of Brazil.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The increase in the prevalence of HAdV may be associated with antigenic drift [52][53][54]. In water matrices, the genotype 41 is also the most prevalent genotype in several regions worldwide such as Michigan, Poland, Norway, South Africa, Tunisia, Taiwan, Singapore, Germany, Italy [10,29,31,32,[55][56][57][58]. These data strengthen the results obtained in this study that also point the genotype 41 as the most prevalent in the capital of Brazil.…”
Section: Discussionsupporting
confidence: 86%
“…Studies assessing the prevalence of HAdVs in wastewater and seasonality have shown conflicting results. This may be explained by the climatic and environmental conditions and linked to the variation and the specificity of the climate in each region [10,30,32,58,59]. Here, the sampling method did not allow the assessment of seasonality, and any conclusion would be mere speculation.…”
Section: Discussionmentioning
confidence: 98%
“…Estimated abundance appeared to be in concordance with the range reported previously by other investigators. Myrmel and coworkers detected 10 5.8 to 10 6.2 genomic copies/L of AdV in a study conducted in Norway [37], while Kuo et al detected approximately 3.8 ± 0.5 × 10 5 viral particles per liter of raw sewage in Taiwan [38]. Similarly, EV concentrations ranged from 10 2.7 copies/L in a New Orleans, US study [39] and as high as 1.5 × 10 5 to 1.2 × 10 8 copies per L in an analysis done in Japan [3].…”
Section: Discussionmentioning
confidence: 99%
“…Enteric adenoviruses are reported to cause 5 to 31% of the infant and child acute gastroenteritis in developing countries and pose a high pathogenic opportunity in immune-compromised patients (Farkas and Jiang, 2006;Magwalivha et al, 2010). Enteric adenoviruses have been detected in surface water and wastewater (Fong et al, 2010;Grondahl-Rosado et al, 2014;Kuo et al, 2015;Qiu et al, 2015), and are listed on Contaminant Candidate List 3 (CCL3) of the U.S. Environmental Protection Agency's Drinking Water Contaminant Candidate List 3-Final Notice (2009). Ultraviolet (UV) irradiation, due to its exceptional germicidal effect toward a wide range of microorganisms with minimal generation of byproducts in water, has been increasingly applied for water and wastewater disinfection (Blatchley et al, 2007;Hijnen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%